2022
DOI: 10.1039/d2mh00008c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electronic doping and traps on carrier dynamics in tin halide perovskites

Abstract: Tin halide perovskites have recently emerged as promising materials for low bandgap solar cells. Much effort has been invested on controlling the limiting factors responsible for poor device efficiencies, namely...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 72 publications
3
46
1
Order By: Relevance
“…Certified power conversion efficiencies of perovskite solar cells (PSCs) have surged from 3.8% to 25.7% in ten years, which makes them one of the most promising candidates for photovoltaic applications. Although there has been an unparalleled enhancement in photovoltaic performance, the degradation caused by various stimuli is still a key challenge in the commercialization of PSCs. , Degradation of PSCs usually starts at the perovskite–hole transport (HTL) and perovskite–electron transport (ETL) interfaces because of the high intrinsic defect density of perovskites and the mismatched energy-level alignment at the interfaces between different layers. Significant efforts to inhibit degradation include contact layer modification, defect passivation, and encapsulation . The use of organic molecules as the interfacial passivation layer has great potential to address the surface defects and facilitate charge extraction. …”
mentioning
confidence: 99%
“…Certified power conversion efficiencies of perovskite solar cells (PSCs) have surged from 3.8% to 25.7% in ten years, which makes them one of the most promising candidates for photovoltaic applications. Although there has been an unparalleled enhancement in photovoltaic performance, the degradation caused by various stimuli is still a key challenge in the commercialization of PSCs. , Degradation of PSCs usually starts at the perovskite–hole transport (HTL) and perovskite–electron transport (ETL) interfaces because of the high intrinsic defect density of perovskites and the mismatched energy-level alignment at the interfaces between different layers. Significant efforts to inhibit degradation include contact layer modification, defect passivation, and encapsulation . The use of organic molecules as the interfacial passivation layer has great potential to address the surface defects and facilitate charge extraction. …”
mentioning
confidence: 99%
“…Theoretical studies on tin halide perovskites suggested that tin‐rich environment may also contribute to the formation of nonradiative recombination‐active deep traps, such as tin interstitials and iodide vacancies. [ 9 ] As we recently showed experimentally, [ 25 ] the reduced PLQY observed in FACsSnI thin films with excess SnX 2 with respect to the pristine sample can be explained by a lower background hole doping, which reduces the pseudo‐monomolecular radiative recombination, and a higher probability of formation of deep‐level traps, which contribute to nonradiative recombination processes.…”
Section: Resultsmentioning
confidence: 84%
“…These two classes of defects and the relative optoelectronic dynamics should be decoupled, however, the high background doping concentration in tin halide perovskites may increase the radiative efficiency of the material, masking other optoelectronic nonradiative recombination processes. [24,25] The addition of excess tin halide in tin perovskites limits the density of background holes, which reduces the radiative rate and opens up the chance for nonradiative recombination channels to become effective, especially at low to medium injection levels. In this work, we report an experimental and theoretical investigation of the defect activity in tin halide perovskite thin films prepared with excess Sn halide by combining the photoluminescence evolution over time under continuous optical excitation with first principles computational modeling of defect formation under light irradiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, owing to the low formation energy of the Sn vacancy ( V Sn ) and the easy oxidation of Sn 2+ , Sn 2+ ‐based perovskites generally suffer from poor stability and unintentional self‐p‐doping effects with high background hole concentrations of >10 17 cm −3 10,11 . To address this issue, the most effective approach is the addition of tin fluoride (SnF 2 ), which can suppress excessive hole density, alleviate Sn 2+ oxidation, and improve film crystallinity/uniformity 10–16 . This process generally requires a relatively large amount of SnF 2 (≥10 mol%) in the precursor, which causes phase segregation and creates deep‐level bulk traps, seriously deteriorating device performance 17,18 …”
Section: Introductionmentioning
confidence: 99%